Metabolomic, proteomic, and transcriptomic changes in adults with epilepsy on modified Atkins diet. Issue 4 (24th February 2023) - Leitner, Dominique F.; Siu, Yik; Korman, Aryeh; Lin, Ziyan; Kanshin, Evgeny; Friedman, Daniel; Devore, Sasha; Ueberheide, Beatrix; Tsirigos, Aristotelis; Jones, Drew R.; Wisniewski, Thomas; Devinsky, Orrin
Abstract: Objective: High‐fat and low‐carbohydrate diets can reduce seizure frequency in some treatment‐resistant epilepsy patients, including the more flexible modified Atkins diet (MAD), which is more palatable, mimicking fasting and inducing high ketone body levels. Low‐carbohydrate diets may shift brain energy production, particularly impacting neuron‐ and astrocyte‐linked metabolism. Methods: We evaluated the effect of short‐term MAD on molecular mechanisms in adult epilepsy patients from surgical brain tissue and plasma compared to control participants consuming a nonmodified higher carbohydrate diet ( n = 6 MAD, mean age = 43.7 years, range = 21–53, diet for average 10 days; n = 10 control, mean age = 41.9 years, range = 28–64). Results: By metabolomics, there were 13 increased metabolites in plasma ( n = 15 participants with available specimens), which included 4.10‐fold increased ketone body 3‐hydroxybutyric acid, decreased palmitic acid in cortex ( n = 16), and 11 decreased metabolites in hippocampus ( n = 6), which had top associations with mitochondrial functions. Cortex and plasma 3‐hydroxybutyric acid levels had a positive correlation ( p = .0088, R 2 = .48). Brain proteomics and RNAseq identified few differences, including 2.75‐fold increased hippocampal MT‐ND3 and trends ( p < .01, false discovery rate > 5%) in hippocampal nicotinamide adenine dinucleotide (NADH)‐related signaling pathways (activated oxidative phosphorylation and inhibited sirtuin signaling). Significance: Short‐term MAD was associated with metabolic differences in plasma and resected epilepsy brain tissue when compared to control participants, in combination with trending expression changes observed in hippocampal NADH‐related signaling pathways. Future studies should evaluate how brain molecular mechanisms are altered with long‐term MAD in a larger cohort of epilepsy patients, with correlations to seizure frequency, epilepsy syndrome, and other clinical variables. [Clinicaltrials.gov NCT02565966.]